2015
DOI: 10.15253/2175-6783.2015000500004
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to the quality of life of diabetic patients

Abstract: Objective: to analyze the association among the variables of socio-demographic, clinical and lifestyle of diabetics, correlating them to the domains of Diabetes Quality of Live-Brazil scale. Methods: a cross-sectional analytical study of 60 diabetic patients enrolled in a primary care unit. The scale has 44 items divided into four domains: Satisfaction, Impact, Social/ Vocational and General concerns related to diabetes. Results: it was found that patients who do not adopt healthy lifestyle habits have improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
0
4
0
5
Order By: Relevance
“…Studies that used DQOL-Brazil to evaluate the HRQL of people with DM2 showed similar characteristics. 4,9,10,14,15 Regarding the patients' age, an average of 62.7 years old was found. Thus, understanding the elderly's quality of life is a complex task.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Studies that used DQOL-Brazil to evaluate the HRQL of people with DM2 showed similar characteristics. 4,9,10,14,15 Regarding the patients' age, an average of 62.7 years old was found. Thus, understanding the elderly's quality of life is a complex task.…”
Section: Discussionmentioning
confidence: 96%
“…32 Despite the relevance of the physical activity to improve the quality of life, studies showed that patients with DM who did not engage in physical activity reported feeling dissatisfied with this domain. 10 In addition, the study indicated that the HRQL is affected by the need to perform exercises regularly. 21 As for the domain of impact, most of the patients pointed out that this domain has never interfered with their quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mais recentemente, o estudo de Lagana [11], também na cidade de Curitiba/PR, com usuários das Unidades Básicas de Saúde do Distrito Portão, computou que 67,2% dos participantes eram mulheres. Em 2015, aplicando o questionário em uma unidade de Atenção Primária à Saúde pertencente à Regional IV no município de Fortaleza/CE, Frota, Guedes e Lopes [12] obtiveram 75% da amostra composta por participantes do sexo feminino. Em 2016, um estudo conduzido na Clínica de Atenção Especializada e em 12 Unidades de Saúde da Família na cidade de Piracicaba/SP por Corrêa [13] observou que 69,5% dos participantes eram mulheres.…”
Section: Discussionunclassified